CLINICAL CHARACTERISTICS OF SQUAMOUS INTRAEPITHELIAL LESION (SIL) PATIENTS AT SANGLAH RSUP DENPASAR 2015-2019 - Patuan, Jonathan Yoshua (E-Jurnal Medika Udayana, 2021)
Cervical cancer is a malignant disease that attacks the cervix uteri. Before the cancer phase, it will begin with precancerous lesions or Squamous Intraepithelial Lesion (SIL), which often do not cause complaints or symptoms. Therefore, regular screening is needed to detect precancerous lesions. One of the most widely used screening programs is the Pap smear method. The purpose of this study was to determine the clinicopathological characteristics of SIL patients at Sanglah Hospital Denpasar in 2018 - 2019. This study was a descriptive study with a cross sectional study design. Total sampling was carried out by collecting secondary patient data recorded in the form archive and the results of the histopathological examination of uterine cervical biopsy at the Anatomical Pathology Laboratory of Sanglah Hospital Denpasar in 2018 - 2019. The patient data collected were in the form of age, biopsy indications, and the degree of SIL. The samples collected in this study were 177 samples of SIL patients, with the most cases in the 41-50 years age category, namely 73 people (41.2%). The mean age of LSIL patients was 41.5 years and HSIL patients were 39.7 years. The findings of the previous abnormal pap smear results as an indication of a biopsy were found to be the most, namely 73 people (41.3%), and the highest degree of SIL was HSIL as many as 94 people (53.1%). Keywords: precancerous lesions, cervix, SIL, Sanglah Hospital Denpasar